A drop of hope - Calabrese, Keith (New York : Scholastic, 2019)
Times are tough in the small town of Cliffs Donnelly, Ohio (sarcastically called If Only) especially for some of the kids at Rod Serling Middle School, but then an old dry well suddenly begins to grant wishes, or so it seems--three of the students, Ernest Wilmette, Ryan Hardy, and Lizzy MacComber, know what is happening (but do they really?), because sometimes a good deed can make magic happen.
In english
Keywords: Wishing wells -- Juvenile fiction; Wishes -- Juvenile fiction; Secrecy -- Juvenile fiction; Helping behavior -- Juvenile fiction; Friendship -- Juvenile fiction; Wishing wells -- Fiction; Wishes -- Fiction; Secrets -- Fiction; Helpfulness -- Fiction; Friendship -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Ohio -- Juvenile fiction; Ohio -- Fiction